Design of cyclometallated 5-π-delocalized donor-1, 3-di(2-pyridyl)benzene platinum(II) complexes with second-order nonlinear optical properties. (8th February 2018) - Baggi, Nicolò; Garoni, Eleonora; Colombo, Alessia; Dragonetti, Claudia; Righetto, Stefania; Roberto, Dominique; Boixel, Julien; Guerchais, Véronique; Fantacci, Simona
Graphical abstract: The novel easily-prepared platinum(II) complex with a cyclometallated 5-styryl-1, 3-di(2-pyridyl)benzene is characterized by a good second-order NLO response, as determined in solution by the EFISH technique and it is a good candidate for application in photonics. Abstract: The effect on the second-order nonlinear optical properties of the nature of the π-delocalized moiety in the position 5 of a 1, 3-di(2-pyridyl)benzene cyclometallated to a platinum(II) center was investigated. The influence of the substitution of a double bond with a triple bond as bridge between a triphenylamino group and the cyclometallated phenyl ring was studied and turned out to be negligible. Remarkably, the novel easily-prepared platinum(II) complex with a cyclometallated 5-styryl-1, 3-di(2-pyridyl)benzene is characterized by a good second-order NLO response, as determined in solution by the EFISH technique; it is a good candidate for application in photonics.